Epistemologies of Care - Ana Cristina Gomes da Rocha (JAm It!)
Bearing in mind Epeli Hauʻofa’s concept of “a sea of islands,” this article proposes an ecocritical analysis of three poems written by three Indigenous authors, Craig Santos Perez (CHamorro-Guam) Jamaica H. Osorio (Hawai’i), and Sia Figiel (Samoa) published between 2016 and 2022, respectively. Together, the poems create a relevant example of Indigenous ecocriticism that is overtly interacting with global flows of power and are simultaneously entangled with the struggles of many other Pacific islanders when it comes to topics such as ecological degradation, land occupation, mass tourism, and militarization/nuclearization of Pacific island-nations. The poems to be analyzed are “Green Washing and White Dollar Policy” (Jamaica H. Osorio), “Praise Song for Oceania” (Craig Santos Perez) and “In-Land-Ness” (Sia Figiel). The epistemologies of care that I am referring to are based on Indigenous ancestral knowledge and practices that are vessels of environmental ethics and honor Earth as an ancestor, as well as demonstrations of multiple forms of belonging in which human and non-human elements are symbiotically connected. Therefore, this article problematizes and critically questions the impact of global policies upon Indigenous communities as well as it presents examples of resistance that are generating transcultural move-ments in which contemporary Indigenous writers question the validity of globalized policies that had proven to be disruptive and harmful for their societies. Each of these authors presents chal-lenging questions that trace environmental degradation back to the colonial encounter while demonstrating that their Indigenous societies developed complex and sustainable relationships with the environment, those that were disrupted by colonialism and subsequently imperialism and globalization. Moreover, the voices of these writers resonate through waves of anger against the harm that has been inflicted upon ecosystems, and thus their poems are ways of denouncing injustices, and, to a certain extent, ensuring cultural survival when assuming a strategic significance as counternarratives to the Americanization of the islands. Consequently, my analysis of the poems aims at demonstrating that coalitions formed among Pacific Islanders vividly respond to the imperial West and fiercely resist land occupation and environmental degradation. Embedded in my analysis is also an assumed critique of colonial/Western views of nature as a separate and empty object that exists to be exploited and to generate profit. In sum, the tapestry woven by the poems selected here highlights the importance of activism, education, care, and love as actions that simultaneously denounce multiple forms of “slow violence” against Indigenous cultures and generate decolonial discourses.